Facilitating English Club For High School Students: “Life to The Max” - Adaninggar Septi Subekti; Mega Wati (LPPM UNINUS, 2020)
This article reports a community service in the form of an English Club programme conducted for students of SMA Immanuel Kalasan, a private High School in Sleman, Yogyakarta. The lecturers of the English Language Education Department (ELED) of Duta Wacana Christian University (UKDW) became the facilitators of the programme with several ELED students being the facilitator assistants. The English Club was conducted in the second semester of the 2018/2019 academic year and it became the third edition of the English Club co-conducted by the school and the ELED. With speaking skill as the target, the programme used the principles of whole-person education in which the focus of the instruction was not only on cognitive aspect, but also on the affective, behavioural, and spiritual aspects. This programme was themed “Life to the Max” and there were in total seven meetings conducted every other Thursday in which each ninety-minute meeting had smaller theme in relation with the big theme. These themes were “communication”, “bullying”, “comparing self to others”, “health”, “sports”, “environment”, and “relationship”. The instruction was in general conducted in a highly communicative way with most of the activities conducted in small groups with the participants making vlogs about the topic being the after-class task. Based on the reflection of what went well and what needed improvement in this programme, some conclusions and recommendations on future programmes were made.